HUBUNGAN MOTIVASI DAN MEKANISME KOPING DENGAN KEPUASAN KERJA PADA PERAWAT - Supirno, Supirno; Sitorus, Jenti; Millati, Rida'; Purnamasari, Salsabila; Hendrik, Hendrik (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2024)
The results of a survey conducted at Prima Hospital 4 out of 10 people said they were not motivated at work and only carried out work only as a demand. This is due to the high workload. Meanwhile, 5 out of 10 people said they had less job satisfaction because they wanted to do good or bad work the same. The purpose of the study was to determine the relationship between work motivation and coping with job satisfaction in nurses at Prima Hospital. This type of quantitative research with a cross sectional approach with a sample of 64 nurses. The data collection tool used was a questionnaire and data analysis with Chi-Square. The results of this study found that there was a relationship between work motivation and job satisfaction with a p value of 0.014, and there was a relationship between coping mechanisms on job satisfaction with a p value of 0.005. The conclusion of the study is that there is a relationship between work motivation and coping mechanisms on job satisfaction in nurses at Prima Hospital. It is recommended that nurses who are research respondents can be used as evaluation material in an effort to increase satisfaction at work at Prima Hospital Pekanbaru.Keywords: Knowledge Level, Socioeconomics, Nutritional Status